2014
DOI: 10.3389/fmicb.2014.00250
|View full text |Cite
|
Sign up to set email alerts
|

Cellular unfolded protein response against viruses used in gene therapy

Abstract: Viruses are excellent vehicles for gene therapy due to their natural ability to infect and deliver the cargo to specific tissues with high efficiency. Although such vectors are usually “gutted” and are replication defective, they are subjected to clearance by the host cells by immune recognition and destruction. Unfolded protein response (UPR) is a naturally evolved cyto-protective signaling pathway which is triggered due to endoplasmic reticulum (ER) stress caused by accumulation of unfolded/misfolded protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 182 publications
(229 reference statements)
1
19
0
2
Order By: Relevance
“…Our results are consistent with a previous study reporting that BiP overexpression attenuates PERK and IRE1 activation, whereas a reduced level of BiP activates the UPR [49,50]. When the ER stress cannot restore the cellular homeostasis, C/EBP homologous protein (CHOP) is activated, leading to cell apoptosis [34,51]. Indeed, we found that CHOP expression was activated in response to VV-Onco induced cell stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with a previous study reporting that BiP overexpression attenuates PERK and IRE1 activation, whereas a reduced level of BiP activates the UPR [49,50]. When the ER stress cannot restore the cellular homeostasis, C/EBP homologous protein (CHOP) is activated, leading to cell apoptosis [34,51]. Indeed, we found that CHOP expression was activated in response to VV-Onco induced cell stress.…”
Section: Discussionsupporting
confidence: 93%
“…The major ER chaperone binding immunoglobulin protein (BiP), also known as glucose-regulated protein78 (GRP78), is the master regulator of the UPR [14,34]. The anti-apoptotic property and cytoprotective function of BiP is well established [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…UPR有3条信号通路分支, 分别由3种内质网 驻膜蛋白所介导, 即IRE1(inositol-requiring protein 1), ATF6(activating transcription factor 6) 和 PERK(protein kinase RNA-like ER kinase). 在正常细胞中, 这3种重要 的信号分子都能够与内质网主要分子伴侣BiP(binding 起始的重要调节因子, 激活的eIF2α会抑制蛋白质的 合成 [51,52] .…”
Section: Vv(cop)δf1lunclassified
“…痘苗病毒的K3L蛋 白由于与eIF2α序列具有约28%的一致性, 因此会被 eIF2α的激酶PKR(pancreatic eIF2α kinase)当做底物从 而抑制了PKR的活性, 阻止了eIF2α的磷酸化. 进一步 研究显示, K3L也能抑制PERK(PKR-like ER kinase)的 活性 [51,55] . 此外, 在RK13和HeLa细胞中, 痘苗病毒K1 蛋白能够抑制病毒诱导的eIF2α的磷酸化和PKR的磷 酸化 [56] , 这些有利于蛋白质的重新合成.…”
Section: Vv(cop)δf1lunclassified
“…This contrasts with most gene therapy approaches which replace functional loss with a WT gene product but do not remove the mutant, allowing the continued impact on the UPR due to the mutant and the viral vector used to insert the replacement gene, even though function may be restored [35]. …”
Section: Therapeutic Advantages Of Pharmacoperone Drugsmentioning
confidence: 99%